Compartmentalized regulation of NAD+ by Di (2-ethyl-hexyl) phthalate induces DNA damage in placental trophoblast - Shuai Zhao; Yun Hong; Yue-yue Liang; Xiao-lu Li; Jiang-chuan Shen; Cong-cong Sun; Ling-luo Chu; Jie Hu; Hua Wang; De-xiang Xu; Shi-chen Zhang; Dou-dou Xu; et al. (Redox Biology, 2022)
Di (2-ethyl-hexyl) phthalate (DEHP) is a wildly used plasticizer. Maternal exposure to DEHP during pregnancy blocks the placental cell cycle at the G2/M phase by reducing the efficiency of the DNA repair pathways and affects the health of offsprings. However, the mechanism by which DEHP inhibits the repair of DNA damage remains unclear. In this study, we demonstrated that DEHP inhibits DNA damage repair by reducing the activity of the DNA repair factor recruitment molecule PARP1. NAD+ and ATP are two substrates necessary for PARP1 activity. DEHP abated NAD+ in the nucleus by reducing the level of NAD+ synthase NMNAT1 and elevated NAD+ in the mitochondrial by promoting synthesis. Furthermore, DEHP destroyed the mitochondrial respiratory chain, affected the structure and quantity of mitochondria, and decreased ATP production. Therefore, DEHP inhibits PARP1 activity by reducing the amount of NAD+ and ATP, which hinders the DNA damage repair pathways. The supplement of NAD+ precursor NAM can partially rescue the DNA and mitochondria damage. It provides a new idea for the prevention of health problems of offsprings caused by DEHP injury to the placenta.